Local People’s Practices in the Tourism Region of Indonesia: Issues, Threats and Solutions - JUNAID, Ilham; SOM, Ahmad Puad Mat (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.10.4(36).12, 2019)
Quality of experience is the tourists’ dream when visiting the beach, island or the coastal area. However, unsustainable practices potentially constrain tourists in obtaining good service from the local people. As a consequence, the tourists’ satisfaction may not be achieved and the local people cannot gain sustainable economic advantages. This paper discusses unsustainable practices that occur in a tourism region called Tanjung Bira Beach, Indonesia. A qualitative study, which was conducted in 2016-2018, provides relevant information about the current practices by the local people, why they behave in such ways and what are their expectations to optimize the positive impacts of tourism. The study reveals that the way local people serve the guests and practice daily activities potentially degrade the quality of the environment. Issues of how boat providers use anchor in managing their boats and serving the guests, the souvenir making process, and water issue need to be tackled by making people aware about their tourism resources and their utilization for their own sustainable benefits. It is argued that three stakeholders (local people, local government and local tourism industries) have the opportunity to improve the quality of service and to protect the tourism resources. This paper offers three approaches that the stakeholders can do to optimize the positive impacts of beach tourism while reducing the unsustainable practices by the local people.